2015
DOI: 10.7773/cm.v41i3.2464
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Sr:Ca ratio and morphometry as indicators of habitat of a euryhaline species: The case of the silverside Odontesthes bonariensis

Abstract: ABSTRACT. The silverside Odontesthes bonariensis is a euryhaline species native of South America and represents a very important fishing resource for the Plata Basin (Argentina and Uruguay). This study compares the Sr:Ca ratio of water as well as the Sr:Ca ratio and morphometry of the sagittal otolith of the silverside present in different environments (one salt lake, two freshwater dams, one lagoon, and one estuary) in order to evaluate the use of these variables as markers of habitat. The pattern of the Sr:C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 36 publications
1
19
0
7
Order By: Relevance
“…Campana & Casselman, 1993;Burke et al, 2008;Cañas et al, 2012;Avigliano et al, 2014), to differentiate species (e.g. Few studies use relationships based on the sulcus such as SS/OS (Gauldie, 1988, Lombarte, 1992Avigliano et al, 2014Avigliano et al, , 2015cJaramilo et al, 2014;Zhuang et al, 2014) Commonly used indexes in this paper such as OL/SuL, circularity and rectangularity were not efficient to characterize the studied species (see PCA, Figure 3). Platt & Popper, 1981;Gauldie, 1988;Lombarte et al, 2003;Volpedo & Echeverría, 2003; Volpedo & Fuchs, 2010;Jaramilo et al, 2014;Avigliano et al, 2015c), as an environmental indicator (Nelson et al, 1994;Avigliano et al, 2012Avigliano et al, , 2015c and to determine fossilized specimens (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Campana & Casselman, 1993;Burke et al, 2008;Cañas et al, 2012;Avigliano et al, 2014), to differentiate species (e.g. Few studies use relationships based on the sulcus such as SS/OS (Gauldie, 1988, Lombarte, 1992Avigliano et al, 2014Avigliano et al, , 2015cJaramilo et al, 2014;Zhuang et al, 2014) Commonly used indexes in this paper such as OL/SuL, circularity and rectangularity were not efficient to characterize the studied species (see PCA, Figure 3). Platt & Popper, 1981;Gauldie, 1988;Lombarte et al, 2003;Volpedo & Echeverría, 2003; Volpedo & Fuchs, 2010;Jaramilo et al, 2014;Avigliano et al, 2015c), as an environmental indicator (Nelson et al, 1994;Avigliano et al, 2012Avigliano et al, , 2015c and to determine fossilized specimens (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the taxonomic value of otoliths is well established (e.g. Platt & Popper, 1981;Gauldie, 1988;Lombarte et al, 2003;Volpedo & Echeverría, 2003; Volpedo & Fuchs, 2010;Jaramilo et al, 2014;Avigliano et al, 2015c), as an environmental indicator (Nelson et al, 1994;Avigliano et al, 2012Avigliano et al, , 2015c and to determine fossilized specimens (e.g. Because of these characteristics, otolith morphometry has been widely used to identify fish stocks (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Sr:Ca ratio of otolith has been widely used to infer migratory and population aspects of several species (Avigliano, Volpedo, 2016); for example Genidens barbus (Avigliano et al, 2015a(Avigliano et al, ,b, 2016a(Avigliano et al, , 2017b, Odontesthes bonariensis (Valenciennes, 1835) (Avigliano, Volpedo, 2013;Avigliano et al, 2014Avigliano et al, , 2015c, Mugil liza Valenciennes, 1836 7 e170055 [7] (Callicó Fortunato et al, 2017), Lycengraulis grossidens (Spix & Agassiz, 1829) (Mai et al, 2014), Micropogonias furnieri (Desmarest, 1823) (Albuquerque et al, 2012) and P. lineatus (Avigliano et al, 2016b(Avigliano et al, , 2017a. Particularly in P. lineatus it has been used the otolith microchemistry (Sr:Ca, Ba:Ca and Zn:Ca ratios) as well as otolith and scales morphometry in order to identify different nursery areas (Avigliano et al, 2016b(Avigliano et al, , 2017a.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, form factor did not showed to be a good indicator for the streaked prochilod, as well as for other species like C. rupestris (Longmore et al, 2010). However, form factor index along with ellipticity index, led to the identification of populations of O. bonariensis (Avigliano et al, 2015e). These discrepancies among different species show that the use of morphologic indices to separate breeding areas or populations is species and/or environmentally dependent, and should be correctly evaluated before their use for monitoring or population studies.…”
Section: Discussionmentioning
confidence: 99%
“…These indices showed to be a good tool as habitat indicators for other species of the same basin, like pejerrey O. bonariensis (Avigliano et al, 2015e) and river croaker Plagioscion ternetzi (Avigliano et al, 2015a). The DA classification percentages are similar to those reported by other authors (Tuset et al, 2003a;Avigliano et al, 2015e), who have indicated that the otolith shape indices can be used as natural markers, not only to separate the species, but also to identify populations or nurseries. Circularity was also a good habitat indicator for other species like Coryphaenoides rupestris (Longmore et al, 2010) and Lophius piscatorius (Cañás et al, 2012).…”
Section: Discussionmentioning
confidence: 99%